VD_FINDINFO Arrêt / 2025 / 682 vom 12. August 2025 - VD Tribunal cantonal (2025)
REJET DE LA DEMANDE, OPPOSITION TARDIVE, RESTITUTION DU DÉLAI, CERTIFICAT MÉDICAL | 38 LPGA, 41 LPGA, 52 al. 1 LPGA, 56 al. 1 LPGA